Implementasi Jaringan Internet Dengan Teknologi Gpon Menggunakan Vlan Pada Pt Quantum Tera Network - Maulana Ali Waliyadin; Hendra Supendar; Riza Fahlapi (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2023)
EOC Network Many hops are traversed from the server to the customer so that the capacity of the old network devices and cables cannot accommodate the customer's bandwidth needs. analysis of new network design using VLAN. Many active devices need to be maintained so that it requires time, effort, and a large budget. Designing a GPON network with the latest technology in an area. Simplify maintenance in the future. Fiber optic cables can contain any number of these fibers. This layer surrounds the fiberglass core. Field review. discussions with related parties and then data is recapitulated which will then become material for further submissions. VLAN allows network administrators to identify, control access, manage devices in a VLAN more easily and organized. By using VLAN access mode. The existence of previous network disturbances using coaxial cable in the process obtained bandwidth. EOC network 46.2 Mbps to 48.9 Mbps if using GPON network. Packet loss is obtained from electromagnetic waves which cause interference with network signals. The GPON network has a larger capacity than the coaxial network. More stable internet service, because packet loss is generated 2% compared to 9% EOC